Lack of correlation of P-glycoprotein expression with response to MIC chemotherapy in oesophageal cancer. Issue 11 (November 1995) - Darnton, S J; Jenner, K; Steyn, R S; Ferry, D R; Matthews, H R
Abstract : The multidrug resistance gene product P-glycoprotein (P-GP) was assessed immunohistochemically (by antibody JSB-1) in biopsy specimens from 27 oesophageal squamous carcinomas and 10 adenocarcinomas before treatment with mitomycin, ifosfamide and cisplatin (MIC). Tumours were assessed following treatment and correlation with response sought. Of the squamous carcinomas, 74% (20/27) responded to MIC but only one expressed P-GP before and after treatment. Of the adenocarcinomas, 30% (three of 10) responded. Seven of the 10 adenocarcinomas expressed P-GP before treatment but all 10 were P-GP positive after chemotherapy. The difference in prevalence and induction of P-GP between the histological types was highly significant and may correlate with the greater response to MIC seen in squamous carcinomas compared with adenocarcinomas. P-GP cannot be used as a predictive marker of response as tumours express it inconsistently with response to MIC. Resistance to MIC may be due to other mechanisms.